Health-related quality of life in severe hypersensitivity reactions: focus on severe allergic asthma and hymenoptera venom anaphylaxis—a cross-sectional study - Ricciardi, Luisa; Silvestro, Orlando; Martino, Gabriella; Catalano, Antonino; Vicario, Carmelo Mario; Lund-Jacobsen, Trine; Schwarz, Peter; Sapienza, Daniela; Gangemi, Sebastiano; Pioggia, Giovanni; Giorgianni, Concetto Mario (Frontiers in Psychology, 2024)
Background: Growing evidence reveals the important role of clinical psychological factors in chronic-immune diseases. The aim of this study was to investigate Health-Related Quality of Life (HR-QoL), depression, anxiety, and alexithymia in patients with severe hypersensitivity reactions such as Severe Allergic Asthma (SAA) and Hymenoptera Venom Anaphylaxis (HVA). Methods: The Short-Form Health Survey-36 (SF-36), the Beck Depression Inventory Questionnaire (BDI-II), the Hamilton Anxiety Rating Scale (HAM-A) and the Toronto Alexithymia Scale (TAS-20) were used to assess HR-QoL and clinical psychological features of patients with SAA and HVA. Results: Overall, 78 patients were recruited. Patients with SAA (n=35) reported lower scores for physical functioning [65 (58–75) Vs 90 (85–95); p = < 0.001], role limitations due to physical health [25 (0–50) Vs 62 (50- 5); p = 0.004], bodily pain [47.5 (41.1–61.3) Vs 55.5 (55-96); p = 0.001], general health [40 (30-60) Vs 70 (50–80); p = 0.0003] and social functioning [50 (37.5–62.5) Vs 62.5 (54.9–75); p = 0.007] while higher scores for depressive symptoms [14 (11-15.4) Vs (9.5 (6–15.4); p = 0.05)] compared to HVA patients (n=43). All the dimensions of SF-36 were negatively correlated with anxiety (r from -0.26 to -0.66; pall <0.01) and depressive symptoms (r from -0.44 to -0.73; pall <0.001). Alexithymia was negatively correlated with vitality (r = -0.28; p = 0.02) and mental health (r = -027; p= 0.03). Additionally, patients with alexithymia (38% of participants) showed higher levels of depressive symptoms [9.5 (10–19) Vs 14 (6–13.9); p = 0.005] and anxiety levels [31 (27.9–35) Vs 24 (16–33.9); p = 0.02]; they also showed less vitality [40 (39.9–50) Vs 55 (50–60) p = 0.01], social functioning [50 (37.5 62.5) Vs 62.5 (50 vs 75); p = 0.01] and mental health [48 (44–60) Vs 68 (56–76); p = 0.004]. Conclusion: Clinical psychological features due to severe hypersensitive reactions may contribute to the patient’s perceived HR-QoL. Focused clinical psychological interventions should be promoted to improve the clinical management of such conditions.